Evidence for the Presence of a Porin in the Membrane of Glyoxysomes of Castor Bean. - Reumann, S. (1997)
Glyoxysomes of endosperm tissue of castor bean (Ricinus communis L.) seedlings were solubilized in a detergent and added to a lipid bilayer. Conductivity measurements revealed that the glyoxysomal preparation contained a porin-like channel. Using an electrophysiological method, which we established for semiquantitative determination of porin activity, we were able to demonstrate that glyoxysomal membranes purified by sucrose density gradient centrifugation contain an integral membrane protein with porin activity. The porin of glyoxysomes was shown to have a relatively small single-channel conductance of about 330 picosiemens in 1 M KCl and to be strongly anion selective. Thus, the glyoxysomal porin differs from the other previously characterized porins in the outer membrane of mitochondria or plastids, but is similar to the porin of spinach (Spinacia oleracea L.) leaf peroxisomes. Our results suggest that, in analogy to the porin of leaf peroxisomes, the glyoxysomal porin facilitates the passage of small metabolites, such as succinate, citrate, malate, and aspartate, through the membrane.